Causal beliefs of mental illness and its impact on help-seeking attitudes: a cross-sectional study among university students in Singapore - Edimansyah Abdin; Siow Ann Chong; Mythily Subramaniam; Shazana Shahwan; Ellaisha Samari; Gregory Tee Hng Tan; Chong Ming Janrius Goh; Wei Jie Ong; Kian Woon Kwok (BMJ Open)
Objectives A considerable proportion of those who suffer from mental illnesses in Singapore do not seek any form of professional help. The reluctance to seek professional help could be due to misconceptions about the causes of mental illnesses. Research has shown that help-seeking attitudes can predict actual service use. As young adults are most at risk of developing mental illnesses, this study aims to elucidate the impact of causal beliefs about mental illness on help-seeking attitudes among university students in Singapore.Design Prior to attending an anti-stigma intervention, data on the Causal Beliefs about Mental Illness, Inventory of Attitudes towards Seeking Mental Health services and questions pertaining to sociodemographic background were collected from participants using a self-administered questionnaire. Multiple linear regressions were performed to examine the relationship between causal beliefs and help-seeking, as well as their sociodemographic correlates.Settings A university in Singapore.Participants 390 students who were studying in a University in Singapore.Results Younger age was associated with higher scores on psychosocial attribution, while prior social contact with individuals with mental illness was significantly associated with lower scores on personality attribution. With regard to help-seeking attitudes; being a male and personality attribution were significantly associated with lower scores on ‘Psychological Openness’ and ‘Indifference to Stigma’, while psychosocial attribution was significantly associated with higher scores on ‘Help-seeking Propensity’. Having prior social contact also predicted higher ‘Psychological Openness’, while being in Year 2 and 3 predicted lower scores on ’Indifference to Stigma’.Conclusion Findings from this study suggest that help-seeking attitudes might be influenced by causal beliefs, with personality attribution being the most impairing. Hence, to reduce the wide treatment gap in Singapore, anti-stigma interventions targeting young people could focus on addressing beliefs that attribute mental illness to the personality of the individual.